Colon-targeting mutual prodrugs of 5-aminosalicylic acid and butyrate for the treatment of ulcerative colitis. Issue 5 (11th January 2018) - Yan, Yan; Sun, Jinyao; Xie, Xianting; Wang, Pengchong; Sun, Ying; Dong, Yalin; Xing, Jianfeng
Abstract : The aim of this study was to design and synthesize four colon-targeting mutual prodrugs of 5-aminosalicylic acid (5-ASA) and butyrate, and evaluate their therapeutic effects on ulcerative colitis. Abstract : The aim of this study was to design and synthesize four colon-targeting mutual prodrugs of 5-aminosalicylic acid (5-ASA) and butyrate, and evaluate their therapeutic effects on ulcerative colitis. Herein, 5-ASB, 5-ASDB, Ols-DB and Ols-DBP were prepared and characterized, and their lipophilicity, solubility, in vitro and in vivo stability were investigated. Finally, the ameliorative effects of the prodrugs on experimental colitis were evaluated via a series of indicators, including the body weight and survival rates of mice, the colon index and colonic damage score, the disease activity index, the myeloperoxidase activity and levels of superoxide dismutase, malondialdehyde, glutathione and glutathione peroxidase in colonic tissues. As a result, 5-ASB was very stable but Ols-DB showed extreme instability in the environment of the gastrointestinal tract, while 5-ASDB and Ols-DBP showed desirable colon-targeting properties. The four prodrugs all had certain therapeutic effects on the experimental colitis. When orally administered to mice, 5-ASDB and Ols-DBP had significantly greater effects than the mixture of 5-ASA and sodium butyrate. Ols-DB was used as an enema and could be as effective as 5-ASDB and Ols-DBP. In addition, the therapeutic effects of the synthesized prodrugs might be associated with their anti-oxidative damage ability.